Ethnography in Malaysia Animation Study: A Case Study on Kampung Boy - Mohd Zahferee , Iezyan Musfirah; Abdul Rani , Mohd Khairul Azahari; Ab Rashid, Maziah (Advances in Humanities and Contemporary Studies, 2023)
Ethnography is a form of qualitative research to analyze and interpret a certain culture within an ethnic group. Ethnographic learning is important to understand ’culture-sharing’. Ethnography provides a detailed understanding of culture, language, arts, and more aspects. In Malaysia, the existence of various ethnic groups allows us to learn the ethnography of other ethnic. However, the understanding of different ethnic is still lacking. Moreover, a lack of understanding and respect for others could cause destruction and harmony in the country. This problem can be controlled by the existence of various media or platforms by applying ethnographic learning, such as animated media. Thus, this study examines how ethnographic learning can be applied in animated media. This paper will study the ethnography of The Kampung Boy animated film by Datuk Lat. In addition, this paper will also discuss the aspect of ethnography, such as the aspect of culture, language, beliefs, arts, and environment, using semiotic theory as a medium to provide an understanding and knowledge of certain ethnic groups. Kampung Boy is one of the animated films about various races and cultures. This film revolves around the adventures of a village boy named Mat and his life in a village.